IS POST-MORTEM HARM POSSIBLE? UNDERSTANDING DEATH HARM AND GRIEF - Tomasini, Floris (Bioethics, 2009)
The purpose of this article is not to affirm or deny particular philosophical positions, but to explore the limits of intelligibility about what post-mortem harm means, especially in the light of improper post-mortem procedures at Bristol and Alder Hey hospitals in the late 1990s. The parental claims of post-mortem harm to dead children at Alder Hey Hospital are reviewed from five different philosophical perspectives, eventually settling on a crucial difference of perspective about how we understand harm to the dead. On the one hand there is the broadly ‘analytical’ tradition1 of thinking that predicates the notion of harm on the basis of an existing subject. Since the dead are non-existent persons, it makes little sense to view the dead as being harmed. On the other hand, there is a phenomenological perspective, where the dead, in respect to the experience of grief, are existentially absent. This forms the basis that it is possible to harm grieving parent's experiences of how their dead are treated. The article ends with a short examination of what harming the dead implies for traditional bioethical concerns, namely, obtaining informed consent from significant others when planning medical research on the newly dead.